2021
DOI: 10.2147/cmar.s303758
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chronic Inflammatory Ratios in Predicting Recurrence of Resected Patients with Stage I–III Mucinous Colorectal Adenocarcinoma

Abstract: Background: Cancer-related inflammation is the main cause of the progression of mucinous colorectal adenocarcinoma (MCA). Circulating fibrinogen-to-pre-albumin ratio (FPR) is associated with the clinical outcome in colorectal cancer (CRC). However, the prognostic role of FPR and which is the best inflammatory prognostic biomarker within MCA remain unknown. Methods: We enrolled 157 patients with stage I-III MCA in this study. Kaplan-Meier curve, Cox regression, and time-dependent receiver operation characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…37 Our findings were consistent with studies evaluating the prognostic value of NPAR in other clinical settings including STEMI, acute kidney injury, septic shock, rectal cancer, mucinous colorectal adenocarcinoma, and cardiogenic shock. [14][15][16][17][18][19] Our study found that NPAR was an independent predictor of all-cause mortality in patients with heart failure. Combined with neutrophils and albumin, NPAR was better than neutrophils or albumin alone in evaluating inflammatory process.…”
supporting
confidence: 47%
See 1 more Smart Citation
“…37 Our findings were consistent with studies evaluating the prognostic value of NPAR in other clinical settings including STEMI, acute kidney injury, septic shock, rectal cancer, mucinous colorectal adenocarcinoma, and cardiogenic shock. [14][15][16][17][18][19] Our study found that NPAR was an independent predictor of all-cause mortality in patients with heart failure. Combined with neutrophils and albumin, NPAR was better than neutrophils or albumin alone in evaluating inflammatory process.…”
supporting
confidence: 47%
“…12,13 Recently, several studies had combined these two markers and found that neutrophil-to-albumin ratio (NPAR) could be used as an inflammation based prognostic predictor in patients with STEMI, acute kidney injury, septic shock, rectal cancer, mucinous colorectal adenocarcinoma, or cardiogenic shock. [14][15][16][17][18][19] However, to our knowledge, no previous studies had explored the prognostic value of NPAR in HF patients. The purpose of this study was to investigate the association between admission level of NPAR and mortality in HF patients by using the Medical Information Mart for Intensive Care III database version 1.4 (MIMIC III v1.4) and the data of the Second Affiliated Hospital of Wenzhou Medical University.…”
Section: Introductionmentioning
confidence: 99%
“…1 . A total of 13 relevant articles were included in this study, including 15 cohort studies and 5116 patients [ 12 24 ]. Unfortunately, we have not found any studies that meet the inclusion criteria from TCGA and GEO databases.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study of 145 individuals with pancreatic adenocarcinoma undergoing palliative treatment, the NPAR was an independent predictor of survival, whereas the platelet-lymphocyte and neutrophil-lymphocyte ratios were not [17]. Similarly, scholars have demonstrated an association between poor survival outcomes and an elevated NPAR in a group of individuals with bladder cancer receiving neoadjuvant chemotherapy and cystectomy [15] as well as in a group of patients receiving surgery for stage I-III colorectal adenocarcinoma [23]. In addition, in a study of 98 patients with rectal cancer receiving neoadjuvant CRT or RT alone, the NPAR independently predicted complete remission [13].…”
Section: Discussionmentioning
confidence: 99%